Notice of some Stone Crosses, with Special Reference to the Market Crosses of Scotland - Drummond, James (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article describes the design, construction and use of mercat crosses in towns across Scotland. There is discussion of the tools that could be used to punish misdemeanours that were often either attached to or near crosses. The author presents the accounts for the construction of a cross in Edinburgh in 1617 to illustrate the kind of money that could be charged for the building of these crosses. There are also some first-hand accounts of events that took place at or near to the mercat cross in Edinburgh. The author briefly touches on the contemporary debate about this cross and whether its design should restore the previous cross that was taken down in 1756, or whether a new design should be produced.